Inclusive Education Mechanisms at UPI Cibiru Laboratory Elementary School (Current Research in Education: Conference Series Journal, 2024)
Inclusive education is education provided for students with special needs. Every school is expected to implement inclusive education as stipulated in government regulations. The purpose of this study is to determine the mechanisms or processes of inclusive education in elementary schools. The research method used is a qualitative research method based on descriptive studies. Data obtained are the results of interviews and observations at SD Laboratorium UPI Cibiru. At the school, there are several students with special needs in each class. The school provides assistant teachers for students with special needs. The school also collaborates with teachers from Special Needs Schools to gain knowledge and methods to develop the potential of students with special needs.